Division in the land of ‘the unspoken’: Examining journalistic practice in contemporary New Caledonia - M’Balla-Ndi, Marie (MedieKultur: Journal of media and communication research, 2017)
While the Kanaks’ (local indigenous population of New Caledonia) pro-independence protests against the French settlers and, more broadly, the French Republic, have been extensively documented in the global media and academic literature, another protest - more subtle and diffused, but deeply embedded - is taking place in New Caledonia. New Caledonia is a South Pacific archipelago colonised by the French in 1853 and set to decide whether to remain in the French Republic or become independent in a referendum between 2014 and 2019. This paper suggests that there is a polarisation in the New Caledonian media sphere, which deeply affects journalistic practices with tendencies to resist Western impositions, standards and dominance (for Kanak journalists and their leaders), while metropolitan journalists (who have settled in New Caledonia from France) tend to often reject customs or indigenous rules shaping general and media communication within local communities. Both tendencies also have a significant impact on which material the journalists will be able to collect for their news organisations, as well as an impact on the relationships these journalists will maintain (or not) with local communities and personalities. This paper examines some aspects of Pacific knowledge (including traditions, values, beliefs and protocols) and explores the nuances of a complex socio-political ‘liquid modern’ context in order to present examples of how developments inherent from tradition, colonisation and decolonisation aspirations, affect the work of local journalists (both metropolitan journalists, and Kanak journalists). Drawing on data collected during periods of archival research, participant observation and interviews conducted at both the metropolitan daily newspaper, Les Nouvelles Calédoniennes, and the pro-independence radio station, Radio Djiido, this paper demonstrates how local journalists problematically navigate, and often contest, diverse socio-cultural values, practices and principles inherent from different times and places/spaces creating a deep division in the New Caledonian media sphere. It is suggested in this paper that Kanak values are often strongly contested by many metropolitan journalists, who often refuse to give any consideration to cultural factors, while, on the other hand, Kanak journalists will often tend to reject some of the principles of Western (or modern) journalism, adjusting these values and/or standards for specific or strategic reasons, such as preserving ‘la coutume’. This paper will also argue that deploying an approach that engages with the concept of liquid modernity, takes into account re-emerging oceanic epistemologies, and that provides a thicker explanation of observed media practices, proves useful for studying journalism in New Caledonia, where culture appears to deeply affect journalism practice on a daily basis.